Connected Facility Quality and Customers Consummation: A learning Study Report of the Selected Commercial Banks in Riyadh (Saudi Arabia) - Al Motairi, Mohammad; Al Meshal, Soad; Alam, Aftab (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Online banking is one of the main functions of modern banking in existing banking operations across the globe. Online banking operations improve the performance of the banking industry and helps customers to reduce their transaction costs. This study aims to investigate the relationship between online banking services offered by Al Rajhi Bank, National Commercial bank and Riyadh Bank. Various dimensions such as movable, tangible assets, reliability, responsiveness and empathy as determinants of customer satisfaction have been used. These dimensions are based on the SERVQUAL model developed by Han and BEC (2004). The reliability and validity of the dimensions were examined by the alpha value of the Cronbach test. The value of this test is 0.74, representing a good internal scale consistency. Descriptive statistics and dichotomous l ogistic regression model have been used to study the relationship various dimensions and customer satisfaction. The sample size is consisting of 100 customers. Purposive sampling technique was used to select customers who familiar with online banking. Thus various university students were selected from the Kingdom of Saudi Arabia in Riyadh. The names of these universities are: King Saud University, University of Islamic Imam Muhammad Bin Saud and Prince Sultan University. The study shows that the selected dimensions; tangible, reliability, responsiveness and empathy are important determinants of overall satisfaction of the customer, but with different levels. Moreover, the study shows that tangible property and reliability to improve most influential dimensions of the overall probability of the customers satisfaction with the rest of the dimensions proposed in this study.